Wiek osadów międzyglinowych na lewym brzegu Warty w Poznaniu w świetle badań palinologicznych - Milecka, Krystyna; Nyćkowiak, Marcin; Troć, Maciej (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2010)
The main aim of this article was to estimate the time of accumulation of organic sediments from Eemian interglacial, found in inter-clay layers. Palynological analysis was done for the samples of sediments. They were taken within the area of Poznań at the sites of geotechnical and geological research. Rebuilding of city-stadium in Bułgarska street was a good opportunity to core the organic sediments interlying the morainic clays which were accumulated during the Mazovian and Vistulian glaciation. Layers lying between the clays contain organic material very often and this was the case this time. Palynological analysis revealed accumulation of these organic sediments during the 5th and 6th period of Eemian Interglacial according to the biostratygraphical classification of Tobolski (1991).
Keywords: Poznań; Interclay deposits; Palynology